"Qawaid-e-Khowar" in Urdu Language: A Critical Study: قواعدِ کھوار" اردو زبان میں:ایک تنقیدی جائزہ" (DARYAFT, 2025)
This article presents a critical study of ‘Qawaid-e-Khowar’, the pioneering grammatical work of Maulana Naqibullah Razi on the Khowar language spoken in the remote district of Chitral, Khyber Pakhtunkhwa, Pakistan. Historically, Khowar has remained underrepresented in linguistic scholarship. The study situates ‘Qawaid-e-Khowar’ within the tradition of Khowar grammar writing and offers a comparative analysis with the earlier work of Prince Samsam-ul-Mulk. It examines the book’s organizational structure, including its treatment of the Khowar alphabet, morphology, word classification, parts of speech, and irregular verb forms. Razi’s use of clear and accessible Urdu, supported by translated Khowar examples, makes the work valuable for both native speakers and non-local learners. Despite earlier Orientalist contributions, a comprehensive grammatical framework for Khowar was lacking. The article concludes that ‘Qawaid-e-Khowar’ fills this significant gap by providing a systematic, pedagogically effective, and foundational model for the study and preservation of Khowar grammar. Overall, ‘Qawaid-e-Khowar’ stands as an influential contribution that establishes a solid foundation for future linguistic research and the preservation of the Khowar language.Conflict of Interest: The authors declare that there are no conflicts of interest related to the research, authorship, and/or publication of this article, and that the data presented have not been fabricated or falsified.Funding: This research did not receive any specific grant or financial support from public, commercial, or not-for profit funding agencies.Participant Consent: The authors confirm that Informed consent was obtained from all participants, and confidentiality was duly maintained.
Keywords: Khowar, language, Grammer, Khowar text with Urdu translations, Qawaid-e-Khowar, Descriptive grammar, Chitral, Regional